DAYA TERIMA DAN ANALISIS KANDUNGAN PROTEIN SERTA KALSIUM BOBA DENGAN PENAMBAHAN TEPUNG QUINOA - Hikmawati Mas'ud; Nana Sabriana; Abdullah Thamrin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Boba is a contemporary drink topping that is popular with teenagers made from tapioca flour, Tapioca itself does not have much taste so the sweet taste of boba is partly from palm sugar which is cooked before serving, this preparation is also very popular in 2020 until now. Boba with the addition of quinoa flour is an alternative to boba products that are high in nutritional value of protein and calcium and do not leave the characteristic of boba which tastes unique and chewy. This study aims to determine how the acceptability and protein and calcium content of boba with the addition of quinoa flour. This research is a pre-experimental research. Protein and calcium content using laboratory tests using Micro Kjedhall and Volumetric methods, then presented in the form of tables and narratives. Based on the Kruskal Walis test, the most preferred color aspect was the addition of 50 grams of quinoa flour, the most preferred aroma aspect was the additionof 30 grams and 50 grams of quinoa flour, the most preferred texture aspect was the addition of 50 grams of quinoa flour, the most preferred taste aspect was 30 grams and 50 grams. Laboratory test results showed that the highest protein and calcium content in the addition of 70 gram quinoa flour was 0.0509 for protein content and 0.378 for calcium content. It is recommended for further research to analyze the content of other nutrients and acceptability to the target community. Keywords : Acceptance, Protein, Calcium, Boba, Quinoa Flour